IMPLEMENTATION OF A GENOTYPE-GUIDED MANAGEMENT PROTOCOL FOR CYTOMEGALOVIRUS INFECTION: PILOT OUTCOMES AND HEALTH ECONOMIC PROJECTIONS IN UZBEKISTAN (International Congress on Economics, Management and Business Studies, 2026)
Cytomegalovirus infection (CMVI) imposes a substantial clinical and economic burden on healthcare systems, particularly in developing countries where seroprevalence approaches 85–95% and resources for prolonged antiviral therapy and rehabilitation are limited (1, 7). Traditional management strategies rely on serial monitoring of viral load and serological markers to guide therapeutic decisions, constituting a reactive approach that identifies deterioration only after it has occurred (3, 6). The cost of treating a single episode of complicated CMVI (pneumonia, encephalitis, generalized infection) in Uzbekistan averages 8–15 million UZS, while long-term rehabilitation of a child with congenital CMVI can exceed 50–80 million UZS annually (7). Wang H. et al. (2020) estimated the global economic burden of congenital CMVI in developing countries at over 1.9 billion USD per year (7), underscoring the magnitude of the problem and the potential value of preventive strategies.